Ativação Muscular Durante a Prática de Terapia de Espelho (TE), Avaliado por Eletromiografia de Superfície em Pacientes Pós-Acidente Vascular Encefálico (AVE) e em um Grupo Controle - Nascimento, Rayssa Silva (2016)
Objective: To analyze muscle activation in post-stroke patients during the practice of mirror therapy (ET). METHODS: This is a cross-sectional observational study. Twenty individuals (9 males and 11 females) were selected who presented a clinical diagnosis of unilateral AVE, age above 18 years, who were not bedridden, with a good seated equilibrium (Berg> 46), who understood simple order. Patients with heminegency, amputated, blind or visually impaired patients who disrupted the study were excluded. These individuals comprised the experimental group (GE). For the control group, 20 individuals (9 males and 11 females) were selected, where they had to be over 18 years old, should understand simple orders, could not have MMSS fractures, pins or plates in the arms, Have a good cognitive rating. Results: The results suggest that the TE is able to increase the muscle recruitment, being observed by the increase of rms verified by surface electromyography. Electromyography was able to prove that mirror therapy promotes an increase in muscle recruitment in both EG and GC, even if the CG did not have any physical impairment. Conclusion: The present study concludes that during rest there is an increase in rms, which was explained by the presence of hypertonia classified by the Ashworth scale. We also suggest that mirror therapy is capable of increasing muscle recruitment measured during surface electromyography because the practice has increased rms values.